Synthesis of Internal Alkynes through the Pd‐Catalyzed Coupling of Heteroaryl Halides with Terminal Alkynes. Issue 9 (6th February 2013) - Lu, Linhua; Yan, Hong; Sun, Peng; Zhu, Yan; Yang, Hailong; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract: Sonogashira‐type cross‐couplings of functionalized heterocyclic halides with terminal alkynes were performed efficiently at room temperature. The heteroaryl halides were easily prepared from the corresponding heterocyclic compounds. The catalytic system tolerated a very broad scope of substrates; oxazoles, thiazoles, and furans participate in this type of reaction for the first time. This reaction provides an efficient method for the direct functionalization of heterocycles. Abstract : Sonogashira‐type cross‐coupling of functionalized heterocyclic halides with terminal alkynes are performed efficiently at room temperature. The catalytic system tolerates a very broad scope of substrates; oxazoles, thiazoles, and furans participate in this type of reaction for the first time. The reaction provides an efficient method for the direct functionalization of heterocycles.